Enzymatic Oxidative Stress Indicators and Oxidative Stress Index in Patients of Leprosy - Raka, Ishita; Rastogi, Madhur Kant; gahalaut, pratik; kaur, jaspreet; mishra, nitin (Nepal Journal of Dermatology, Venereology & Leprology, 2018)
Introduction: Leprosy is a chronic granulomatous disease caused by Mycobacterium leprae. Oxidative stress caused by Reactive oxygen species (ROS) plays a crucial role in the pathogenesisis of leprosy. Objective: To measure the enzymatic oxidative stress indicators and oxidative stress index in patients of leprosy and compare them with healthy age & sex matched controls. Materials and Methods: In this prospective study 30 untreated leprosy patients were included in the study and matched with 60 healthy controls. Biochemistry estimation was done with blood samples and MDA (lipid peroxidation), Nitric oxide (NO), (SOD) Superoxide dismutase (antioxidant enzyme), total oxidant status (TOS), total antioxidant status(TAS) and oxidative stress index (OSI) were estimated. Results: Highly significant rise (p<0.0001) in serum MDA, NO, TOS and OSI was seen in leprosy patients when compared with controls with highly significant decline in SOD and TAS. Conclusion: The study confirms the oxidative stress in leprosy and suggests antioxidant therapy may be used as an adjuvant in the treatment of leprosy along with MDT.